Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, Dan Kebijakan Dividen Terhadap Biaya Agensi (Studi Empiris pada Perushaan Manufaktur Yang Terdaftar di Bursaa Efek Indonesia Periode 20218-2020) - Melati Puspita Sari; Ahmad Soleh; Rinto Noviantoro (UNIVED Press, 2022)
This study was appointed to determine the effect of instutional ownership, managerial ownership, and dividend policy on agency cost in manufacturing companies that have been listed on the Indonesia stock exchange during the 2018-2020. The sample in this study consisted of 13 manufacturing companies listed on the Indonesia stock exchange (IDX) during 2018-2020 which had been selected from certain criteria using the purposive sampling method. ith an observation period of 39 samples. From the research pbtained based on the regression output, the adjusted R square (R2) value of 0,179 in obtained, this is equal to 17,9% of the variation that can be explained by the independent variables. and the remaining 82,1% is explained by factors outside the independent variables.